Effectiveness of Moxibustion for Breech Presentation: A Prospective Study - Sarsmaz, Kemal; Kulah, Belkiz Berna; Orgul, Gokcen; Tonyalı, Nazan Vanlı; Yucel, Aykan; Tekin, Ozlem Moraloglu (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective To evaluate the moxibustion for turning fetuses from breech to vertex presentation.Materials and Methods This was a single-center prospective study. All pregnant women carrying a fetus in breech presentation between the 32 and 35 gestational weeks were offered moxibustion application. The primary outcomes were vertex presentation at 37 weeks of gestation, vertex presentation at birth, and vaginal birth rates. A secondary analysis was performed to understand the effect of parity, type of breech presentation, body mass index (BMI), placental location, gender, and fetal birth weight on the presentation at birth.Results There were 63 cases in the study group and 245 cases in the control group. The rate of vertex presentation at term was found to be higher in the moxibustion group compared to controls (66.7 vs. 48.2%, p=0.022). There were 45 (71.4%) and 131 (53.5%) fetuses with vertex presentation at birth in the study and control groups, respectively (p=0.020). Overall, vaginal delivery rate was higher in the study group (50.8 vs. 37.1%, p=0.048). Multiparity and higher birth weight were associated with increased rates of vertex presentation in the moxibustion and control groups.Conclusion Moxibustion application increased the rate of vertex presentation at birth and also vaginal delivery rate compared with expectant management. Offering moxibustion between the 32nd and 36th week of gestation may provide women with a singleton fetus in breech presentation an opportunity for a vaginal birth.
Keywords: Breech presentation; Cesarean section; External cephalic version; Moxibustion